Métodos combinados para la estimación de parámetros en señales de espectroscopía de resonancia magnética - Cancino De Greiff, Héctor Fernando; Nieto Ramírez, Víctor A. (Ingeniería, 2003)
In this work we develop some parameter and spectral estimation methods in Magnetic Resonance Spectroscopy Signals (MRS). We do this with a dual purpose: first, to enable the full estimation process for the constituent parameters of the time-domain msignal: Amplitude, frequency, damping constant and phase. Second, to generate the parameter estimation in the frequency domain in order to evaluate the effect of the application of time domain estimation methods [2].